Novel active magnetorheological knee prosthesis presents low energy consumption during ground walking. (August 2021) - de Andrade, Rafhael Milanezi; Martins, Jordana Simões Ribeiro; Pinotti, Marcos; Filho, Antônio Bento; Vimieiro, Claysson Bruno Santos
This study analyses the energy consumption of an active magnetorheological knee (AMRK) actuator that was designed for transfemoral prostheses. The system was developed as an operational motor unit (MU), which consists of an EC motor, a harmonic drive and a magnetorheological (MR) clutch, that operates in parallel with an MR brake. The dynamic models of the MR brake and MU were used to simulate the system's energetic expenditure during over-ground walking under three different working conditions: using the complete AMRK; using just its motor-reducer, to operate as a common active knee prosthesis (CAKP), and using just the MR brake, to operate as a common semi-active knee prosthesis (CSAKP). The results are used to compare the MR devices power consumptions with that of the motor-reducer. As previously hypothesized, to use the MR brake in the swing phase is more energetically efficient than using the motor-reducer to drive the joint. Even if using the motor-reducer in regenerative braking mode during the stance phase, the differences in power consumption among the systems are remarkable. The AMRK expended 16.3 J during a gait cycle, which was 1.6 times less than the energy expenditure of the CAKP (26.6 J), whereas the CSAKP required just 6.0 J.